ATP-Dependent C–F Bond Cleavage Allows the Complete Degradation of 4-Fluoroaromatics without Oxygen - Oliver Tiedt (American Society for Microbiology, 2016)
ABSTRACT Complete biodegradation of the abundant and persistent fluoroaromatics requires enzymatic cleavage of an arylic C–F bond, probably the most stable single bond of a biodegradable organic molecule. While in aerobic microorganisms defluorination of fluoroaromatics is initiated by oxygenases, arylic C–F bond cleavage has never been observed in the absence of oxygen. Here, an oxygen-independent enzymatic aryl fluoride bond cleavage is described during the complete degradation of 4-fluorobenzoate or 4-fluorotoluene to CO2 and HF in the denitrifying Thauera aromatica: the ATP-dependent defluorination of 4-fluorobenzoyl-coenzyme A (4-F-BzCoA) to benzoyl-coenzyme A (BzCoA) and HF, catalyzed by class I BzCoA reductase (BCR). Adaptation to growth with the fluoroaromatics was accomplished by the downregulation of a promiscuous benzoate-CoA ligase and the concomitant upregulation of 4-F-BzCoA-defluorinating/dearomatizing BCR on the transcriptional level. We propose an unprecedented mechanism for reductive arylic C–F bond cleavage via a Birch reduction-like mechanism resulting in a formal nucleophilic aromatic substitution. In the proposed anionic 4-fluorodienoyl-CoA transition state, fluoride elimination to BzCoA is favored over protonation to a fluorinated cyclic dienoyl-CoA. IMPORTANCE Organofluorides are produced as pesticides, pharmaceuticals, and other chemicals and comprise approximately one quarter of all organic compounds in the pharmaceutical and agricultural sectors; they are considered a growing class of environmentally relevant persistent pollutants. Especially in the case of fluoroaromatics, biodegradation is hampered by the extreme stability of the arylic C–F bond. In aerobic microorganisms, degradation proceeds via oxygenase-dependent C–F bond cleavage reactions, whereas the enzymes involved in the degradation of fluoroaromatics at anoxic sites are unknown. Here we report a strategy for the complete biodegradation of a fluoroaromatic to CO2 and HF in a denitrifying bacterium via activation to a CoA ester, followed by oxygen-independent arylic C–F bond cleavage catalyzed by an ATP-dependent enzyme. This reaction, in conjunction with a transcriptional adaptation to fluorinated growth substrates, is essential for the anoxic biodegradation of 4-fluorobenzoate/4-F-toluene and probably other fluoroaromatics.